PERSEPSI MAHASISWA PGSD TERHADAP PEMBELAJARAN DARING PADA MATA KULIAH PENDIDIKAN BAHASA DAERAH DI SEKOLAH DASAR - Wendri Wiratsiwi (Universitas Muria Kudus, 2022)
The purpose of this study was to determine the perception of PGSD students of class 2019 on the implementation of online learning during the Covid 19 pandemic in Regional Language courses in elementary schools and to find out the applications used during online lectures, as well as to determine the factors that hindered the implementation of online learning. in the Regional Language course in elementary school.The research method used is descriptive quantitative research with research instruments in the form of questionnaires distributed online via google form. The subjects in this study were PGSD students in the third semester of the class of 2019, totaling 106 students. Data collection used a closed questionnaire method consisting of 4 groups of questions representing aspects of participation in online lectures, the use of online media/online learning applications, the choice of using online learning applications, and barriers to online learning. The research data were analyzed using descriptive quantitative analysis of the percentage technique directly from the google form.The results showed that 94.3% of students took online learning in Regional Language courses at elementary school from home, 88.7% of students used data packages during online lectures, 91.5% of students had moderate internet signal conditions, 96.2 % of students choose cellphones as the media that are often used, 86.8% of students prefer to use google classroom than googlemeet during online learning, 50% of students can understand the material provided, 89.6% of students complain about internet network problems as an obstacle in online learning, and 95, 3% of students expect lectures to be held online and offline during the Covid-19 pandemic.